Road Safety - World Bank (Washington, DC, 2012)
In 1999, between 750 000 and 880 000 persons died in road crashes worldwide, and another 23 to 34 million people were injured. The situation is particularly critical in low and middle income countries (LMCs) where about 86 percent of deaths from road traffic injuries occur even though these countries account for only 40 percent of all motor vehicles. The graph shows that the situation has been worsening in LMCs since 1987. There are strong social, health and economic reasons to reduce the burden of road traffic injuries (RTIs): a) casualties affect mostly economically active persons and have a ripple effect on their dependents, causing suffering and poverty; and b) crash victims represent between 30 and 86 percent of all trauma admissions. They tend to stay in hospital longer than average patients. Developed countries have been relatively successful in reducing the burden of RTIs. This shows that more, better targeted and sustainable investment can prevent RTIs and reduce the damage that results from crashes. Poorer countries clearly need a new and broader approach to road safety.